2021
DOI: 10.1021/acsami.1c07323
|View full text |Cite
|
Sign up to set email alerts
|

Immune/Hypoxic Tumor Microenvironment Regulation-Enhanced Photodynamic Treatment Realized by pH-Responsive Phase Transition-Targeting Nanobubbles

Abstract: Due to a special pathological type of triple-negative breast cancer (TNBC) and the lack of expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (Her 2), targeted therapies are not effective. The lack of effective treatment drugs and insensitivity to the current single-treatment methods are the biggest problems that we face with the TNBC treatment. Therefore, new strategies to achieve selective treatment and further visual efficacy evaluation will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…For example, multiple combined anticancer treatments have been developed using nanobubbles loaded with sonosensitizers and immune checkpoint inhibitors. Antitumor immunity has been markedly improved with NB formulations via the maturation of dendritic cells and the activation of CD8 + cytotoxic T cells both in vitro and in vivo [ 51 53 ]. In this work, chitosan-shelled perfluoropentane-cored NBs that are functionalized with either anti-CD11c or anti-CD1a monoclonal antibodies have been purposely designed for targeted cancer vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, multiple combined anticancer treatments have been developed using nanobubbles loaded with sonosensitizers and immune checkpoint inhibitors. Antitumor immunity has been markedly improved with NB formulations via the maturation of dendritic cells and the activation of CD8 + cytotoxic T cells both in vitro and in vivo [ 51 53 ]. In this work, chitosan-shelled perfluoropentane-cored NBs that are functionalized with either anti-CD11c or anti-CD1a monoclonal antibodies have been purposely designed for targeted cancer vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Nanobubbles have recently been investigated as a means to activate immune systems [ 51 53 ]. For example, multiple combined anticancer treatments have been developed using nanobubbles loaded with sonosensitizers and immune checkpoint inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Although tumors acquire energy predominantly via the “Warburg effect” [ 59 ], seriously accelerated OXPHOS was still observed in considerable malignant cell lines during tumorigenesis, development, and metastasis [ 60 , 61 ]. Consequently, diverse mitochondria respiratory chain inhibitors, including α-tocopherol succinate [ 62 ], papaverine [ 63 ], atovaquone [ 64 , 65 , 66 , 67 , 68 ], tamoxifen [ 69 , 70 ], metformin [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ], and nitric oxide (NO) [ 78 , 79 , 80 , 81 ], have been used for reducing oxygen consumption and increasing PDT efficiency. For example, a nanoplatform was prepared through incorporating L-Arginine and a photosensitizer chlorin e6 with poly-lactic-co-glycolic acid (PLGA) ( Figure 6 ) [ 79 ].…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%
“…The results showed that in contrast mode and fluorescence imaging, the nanobubbles had high gray-scale intensity and their ability to aggregate also increased. 124 To conclude their findings, an A10-3.2 aptamer and loaded PTX-PLGA multifunctional theranostic agent was synthesized for the ultrasound imaging of cancer, which was also used as therapy. 125 D. Le Broc-Ryckewaert et al formulated nanoparticles loaded with paclitaxel with a size in the range of 49–95 nm together with charged surfaces, which were synthesized without the use of any surfactant or detergent.…”
Section: Recent Applications Of Ptx Nanomedicine For the Treatment Of...mentioning
confidence: 99%